2003
DOI: 10.3171/jns.2003.99.6.1004
|View full text |Cite
|
Sign up to set email alerts
|

A prospective controlled study of sleep respiratory events in patients with craniovertebral junction malformation

Abstract: Object. Craniovertebral junction malformation (CVJM) or Chiari malformation in adults, with or without syringomyelia and basilar invagination, produces neuronal dysfunction of the brainstem, cerebellum, cranial nerves, and upper spinal cord. The respiratory center and some of its afferent and efferent components can be altered in these diseases. The authors studied patients with and without CVJM to determine whether this physical feature contributed to sleep disturbances. Methods. Respiratory manifestations du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
34
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 35 publications
5
34
0
5
Order By: Relevance
“…Systematic studies with polysomnography in patients with a Chiari malformation have shown that the rate of sleep-disordered breathing ranges from 59% to 70%. 10,11 Furthermore, recent reports have shown that decompressive surgery decreased sleep-disordered breathing, improving the sleep apnea index in a significant number of patients. 12 The presence of a syrinx usually causes additional deficits such as dissociated sensory loss, segmental weakness, hyperactive reflexes, long tract symptoms, or cranial nerve palsy.…”
Section: Discussionmentioning
confidence: 98%
“…Systematic studies with polysomnography in patients with a Chiari malformation have shown that the rate of sleep-disordered breathing ranges from 59% to 70%. 10,11 Furthermore, recent reports have shown that decompressive surgery decreased sleep-disordered breathing, improving the sleep apnea index in a significant number of patients. 12 The presence of a syrinx usually causes additional deficits such as dissociated sensory loss, segmental weakness, hyperactive reflexes, long tract symptoms, or cranial nerve palsy.…”
Section: Discussionmentioning
confidence: 98%
“…Cases of spontaneous respiratory collapse in adult and infant Chiari type I patients have been well documented, resulting in some deaths 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the association between CM and SAS has been described previously in case report studies610 ranging from acute respiratory failure to central and obstructive apnoeas and hypopnoeas during sleep. Only one study of 23 CM affected patients included a control group 11. In this latter report, including only adults and CM type I, the presence of SAS (defined as apnoea/hypopnoea index values greater than 5) was observed in 44% and 60% of CMI patients, respectively, with and without syringomyelia, and therefore higher than in the control group with 12% of patients affected 11.…”
mentioning
confidence: 83%
“…Only one study of 23 CM affected patients included a control group 11. In this latter report, including only adults and CM type I, the presence of SAS (defined as apnoea/hypopnoea index values greater than 5) was observed in 44% and 60% of CMI patients, respectively, with and without syringomyelia, and therefore higher than in the control group with 12% of patients affected 11. Another recent study on 16 adults affected with CM type I reported the presence of SAS (defined as apnoea/hypopnoea index values greater than 10) in 75% of cases 12.…”
mentioning
confidence: 99%